RESPON PESERTA DIDIK TERHADAP PEMBELAJARAN DARING PADA MATA PELAJARAN BIOLOGI - Fitriah, Fitriah; Adnan, Adnan; Rahma Sya’bani M, Nurhusni; Afidah Tulutfiah, Besse; Indryastuti Sulaeman, Danty; Nurlinda, Nurlinda; Aulia Irzal , Ummul; Bin Jamaluddin, Asham; Aldi, Suhardi (FKIP, Universitas Muslim Maros, 2025)
This study aims to describe students' responses to online learning, especially in biology learning which was carried out on students of class XI Mipa at SMAN 20 Makassar as many as 68 students. This study used a qualitative approach with descriptive qualitative research. The instrument used in the study was a questionnaire sheet consisting of four indicators. The indicators in question are (1) learning quality, (2) suitability of learning levels, (3) incentives, and (4) learning time. The results of the response questionnaire given to students show that most of them feel comfortable and effective in online learning. The level of incentives that learners receive from online learning in biology subject is enough to motivate them to actively participate in learning according to their needs in biology subject. However, there are some aspects such as learning quality that need to be improved. Factors such as the quality of online learning materials, technology support, and teacher involvement have a significant impact on learners' responses. This research provides valuable insights for the development of more effective and supportive online learning for learners in the future. Based on the results of the questionnaire analysis of students' responses to online learning, it can be concluded that the highest indicator obtained a percentage of 64.3% with a good category and the lowest indicator obtained a percentage of 64.3% with a good category.